EFFICACY OF GLYCOSAMINOGLYCANS IN PAPAIN INDUCED OSTEOARTHRITIS RAT MODEL IN RELATION TO HISTOLOGICAL LESIONS SCORING - H. M. Khan; M. Ashraf; M. D. Ahmad; A. S. Hashmi; N. H. Syed; A. A. Anjum (Journal of Animal and Plant Sciences, 2014)
The aim of study was to evaluate efficacy of extracted Chondroitin Sulfate (CS) from chicken keel cartilages, its comparison with standard CS from shark origin alone and in combination with Glucosamine Sulfate (GS) in developed and standardized papain induced Osteoarthritis (OA) rat model. Control group (normal) received sterile normal saline solution while experimental group’s papain intra-articularly. Induction of OA in relation to time was assessed on the basis of histological lesions scores.  Statistical mean histological lesions score on 28th day of post papain injection in OA rats was 12.82±1.64. On the basis of data obtained, 29th day of post papain injection was decided as cut off point for starting the therapy for OA.  Efficacy of treatments among control and OA groups (un-treated and treated) was assessed on the basis of histological lesions scores. Treatments started from 29th day were continued till 60th day of post papain injection. Histological lesions score was not reduced in cartilages of un-treated OA group. In treated groups, structural changes reduced and were found to be close to the normal (control) group. Highest histological lesions score was observed in un-treated OA group followed by GS treated, standard CS, extracted CS, extracted CS plus GS and standard CS plus GS. Maximum reduction in histological lesions score was noted in groups treated with combinations. Histological lesions score of group treated with standard CS (shark) was not significantly different from extracted CS (chicken) alone and extracted CS plus GS. CS extracted from chicken keel cartilages proved to be effective in reducing OA progression. Extracted CS in combination with GS was comparable with standard CS plus GS in efficacy. Chicken keel cartilage is found to be easily available and potential source of CS that may be used as therapeutic agent in OA.
Keywords: Chondroitin Sulfate; Glucosamine Sulfate; Osteoarthritis; cartilage and histological lesions